RETRACTED: Integration of nature, ecology and health concepts - Abuzalova Mehriniso; Sayfullayeva Ra’no; Gaybullayeva Nafisa (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001